Analisis Produktivitas Usaha Perikanan Budidaya dalam Karamba Jaring Apung di Kawasan Waduk Cirata Kabupaten Cianjur (Studi Kasus: Desa Bobojong, Kecamatan Mande) - Mariam, Ery; Suryana, Asep Agus Handaka; Nurruhwati, Isni; Nurhayati, Atikah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This research was conducted in the Mande District, Purwakarta Regency, with the research period from December 2024 to June 2025. The objective of this study is to analyze the factors that can influence the productivity of aquaculture in floating net cages (KJA). The sampling method used in this study was purposive sampling, while the data obtained were analyzed using both descriptive qualitative and quantitative methods. Based on the analysis of productivity levels in aquaculture at Cirata Reservoir, Bobojong Village, Mande District, Cianjur Regency, productivity per unit area was 25.15 kg/m²/year, and productivity per cost unit was Rp. 21,111/kg. The financial analysis resulted in an R/C ratio of 1,10, indicating profitability. The results of the simultaneous (F-test) analysis showed that the F-value for productivity per unit area was 0.003, and the F-value for productivity per unit cost was 0.000. The factors affecting productivity include land area, seed quality, feed conversion, and experience duration, while age had no significant impact.